The retropharyngeal reduction plate for atlantoaxial dislocation: a finite element analysis - Kong, Weiqing; Du, Yukun; Li, Jianyi; Shao, Jiale; Xi, Yongming (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: To investigate the biomechanical properties of the retropharyngeal reduction plate by comparing the traditional posterior pedicle screw-rod fixation by finite element analysis. Methods: Two three-dimensional finite element digital models of the retropharyngeal reduction plate and posterior pedicle screw-rod fixation were constructed and validated based on the DICOM (Digital Imaging and Communications in Medicine) data from C1 to C4. The biomechanical finite element analysis values of two internal fixations were measured and calculated under different conditions, including flexion, extension, bending, and rotation. Results: In addition to the backward extension, there was no significant difference in the maximum von Mises stress between the retropharyngeal reduction plate and posterior pedicle screw fixation under other movement conditions. The retropharyngeal reduction plate has a more uniform distribution under different conditions, such as flexion, extension, bending, and rotation. The stress tolerance of the two internal fixations was basically consistent in flexion, extension, left bending, and right bending. Conclusion: The retropharyngeal reduction plate has a relatively good biomechanical stability without obvious stress concentration under different movement conditions. It shows potential as a fixation option for the treatment of atlantoaxial dislocation.